Psychoanalysis and art, duality and integration. The two Fridas: from the imaginary friend to the masterpiece (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2021)
A simple game that becomes the route of our lives is what Las dos Fridas means, an emblematic work of Mexican surrealism.